Formation and evolution of black holes in the galaxy : Selected papers with commentary - Bethe, Hans Albrecht; Brown, Gerald Edward; Lee, Chang-Hwan (Singapore World Scientific, 2003)
This invaluable book contains 23 papers on astrophysics, chiefly on compact objects, written over 23 years. The papers are accompanied by illuminating commentary.
Includes bibliographical references
Keywords: Cơ bản